2016
DOI: 10.2174/0929867323666160210130256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Biomarkers of Acute Kidney Injury: The Possibilities and Limitations

Abstract: Despite the recent findings concerning pathogenesis and novel therapeutic strategies, the mortality rate in patients with acute kidney injury (AKI) remains very high. Early detection of patients with impaired renal function may help to ensure more aggresive treatment and to improve clinical outcome. Serum creatinine is still gold standard of kidney injury, although it is well known as an insensitive and unreliable biomarker (for example, its concentration does not increase significantly until about half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 0 publications
1
31
0
4
Order By: Relevance
“…It has a transmembrane domain and a short intracellular domain that contains a signaling protein for tyrosine phosphorylation (KIM-1b) [15]. The extracellular domain of KIM-1 is shed from the cell surface by a metalloproteinase-dependent process [81].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…It has a transmembrane domain and a short intracellular domain that contains a signaling protein for tyrosine phosphorylation (KIM-1b) [15]. The extracellular domain of KIM-1 is shed from the cell surface by a metalloproteinase-dependent process [81].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…SCr is an integrator of various intrarenal and extrarenal functions, and its concentration indicates the balance between creatinine generation and excretion [12]. SCr not only is a delayed and insensitive biomarker of changes in kidney function [13], but its concentration does not differentiate structural kidney damage and functional hemodynamic triggers and could be affected by many factors [14,15]. In addition, patients with reduced muscle mass may not have a robust rise in SCr despite a substantial kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new AKI biomarkers of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) were found to be more reliable and sensitive than BUN and creatinine in a number of experimental and clinical studies [25,26]. Compared with the vehicle group, APAP treatment enhanced the mRNA levels of NGAL and KIM-1 by 347-and 5-fold, respectively ( Fig.…”
Section: Rotenone Treatment Blocked the Upregulation Of Tubular Injurmentioning
confidence: 99%
“…Therefore, there is an urgent demand for identification of more sensitive and reliable biomarkers, which may better predict minor kidney injury during drug development and chemical safety testing. Recently, it has been reported that tests for measuring levels of new biomarkers of acute kidney injury, such as kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), cystatin-C, and interleukin-18, are more favorable than tests for BUN and creatinine levels in several experimental and clinical systems [67]. …”
mentioning
confidence: 99%